O metaforze „zza szyby” - Olejniczak, Józef (Przestrzenie Teorii, 2024)
The paper – referring to the poems by Aleksander Wat and Stanisław Barańczak, in which the metaphor of observing the world “from behind the glass” appears – describes the evolution of the way the metaphor was defined. The author traces this evolution in disputes from the time of structuralism, which dominated the literary methodology, to the contemporary “postmodern” position. The fundamental hypothesis and postulate at the same time is a radical turn towards interpretation, i.e. a procedure that places a poetic text again at the center of the discourse, at the expense of increasingly abstract theoretical disputes. Interpretation is understood here as asking questions and multiplying doubts in search of the sense and meanings of poetry.